Tìm m, biết: x^4 – x^3 + 6x^2 – x + m = (x^2–x+5) (x^2+1).

Question

Tìm m, biết: x^4 – x^3 + 6x^2 – x + m = (x^2–x+5) (x^2+1).

in progress 0
Allison 1 năm 2021-08-09T23:30:06+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-08-09T23:31:16+00:00

    Đáp án:

     `m=5`

    Giải thích các bước giải:

    Ta có:

    `(x^2 – x + 5) (x^2 + 1)`

    `= x^4 + x^2 – x^3 – 2 + 5x^2 + 5.`

    `= x^4 – x^3 + 6x^2 – x +5.`

    Vậy `m = 5`.

    0
    2021-08-09T23:31:30+00:00

    Đáp án: `m=5` 

    Giải thích các bước giải:

    `x^4-x^3+6x^2-x+m=(x^2-x+5)(x^2+1)`

    `<=>x^4-x^3+6x^2-x+m=x^4-x^3+6x^2-x+5`

    `<=>x^4-x^3+6x^2-x+m-x^4+x^3-6x^2+x-5=0`

    `<=>(x^4-x^4)+(-x^3+x^3)+(6x^2-6x^2)+(-x+x)+m=5`

    `<=>0+0+0+0+m=5`

    `<=>m=5`

    Vậy `m=5`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )